2014
DOI: 10.2139/ssrn.2523510
|View full text |Cite
|
Sign up to set email alerts
|

Goals as Reference Points in Marathon Running: A Novel Test of Reference Dependence

Abstract: In a large-scale field study of marathon runners, we test whether goals act as reference points in shaping the valuation of outcomes. Theories of reference-dependent preferences, such as Prospect Theory, imply that outcomes that are just below or just above a reference point are evaluated differently. Consistent with the Prospect Theory value function, we find that satisfaction as a function of relative performance (the difference between a runner's finishing time goal and her actual finishing time) exhibits l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
2
10
0
Order By: Relevance
“…convex below the reference point and concave above it. In line with Markle et al (2014) and Allen et al (2014), our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals. With this paper we make novel and significant contributions to research in two ways: (1) by providing field evidence for the applicability of the Heath et al (1999) model to predict user performance in the presence of 'mere' goals;…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…convex below the reference point and concave above it. In line with Markle et al (2014) and Allen et al (2014), our results thus support the transferability of the main properties of the prospect theory value function to goal behavior in the field and suggest a distinct shape of the value function around goals. With this paper we make novel and significant contributions to research in two ways: (1) by providing field evidence for the applicability of the Heath et al (1999) model to predict user performance in the presence of 'mere' goals;…”
Section: Introductionsupporting
confidence: 92%
“…However, they find that the shape of the distribution of the finishing times can be modeled with standard prospect theory parameter estimates. With our paper we complement the work of Markle et al (2014) and Allen et al (2014) by providing field evidence for the applicability of Heath et al's (1999) model to predict user performance in the presence of 'mere' goals. In particular, we answer the following research question: Do individual performance patterns exhibit the main properties of the prospect theory value function (i.e., reference point dependence, loss aversion, and diminishing sensitivity) in the days surrounding 'mere' goal achievement?…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Reference points play an important role in some surprising areas. For example, it has been found that the finishing times of marathon runners bunch around certain reference point times (Allen, Dechow, Pope, & Wu, 2015;Markle, Wu, White, & Sacket, 2015).…”
Section: Analog Processing Explanation For Ldementioning
confidence: 99%
“…In addition to the economic theory literature, there is an increasing number of empirical studies investigating the effects of goal setting on performance in the laboratory and in the field. See for instance Brookins et al (), Corgnet et al (, ), Dalton et al (), Koch and Nafziger (), Markle et al (), and Uetake and Yang (), and for experimental studies about goal setting with university students, see e.g., Clark et al (), Dobronyi et al (), and Van Lent and Souverijn (). In Van Lent and Souverijn () goals are set during one‐on‐one interviews between students and their randomly assigned mentor.…”
Section: Introductionmentioning
confidence: 99%